Undifferentiated hepatic carcinoma with osteoclast-like giant cells: A case report and literature review - Deng, Yujiao; Wang, Ya; Zhang, Yan; Yang, Na; Ji, Xingli; Wu, Bing (Frontiers in Oncology, 2023)
Osteoclast-like giant cell tumor(OGCT) is a common bone tumor, occasionally observed in some extraosseous organs, but rarely involving the digestive systems, especially for liver. Previously reported osteoclast-like giant cell carcinoma of the liver often coexists with sarcomatoid or hepatocellular carcinoma. Undifferentiated liver tumor with Osteoclast-like giant cells(OGCs) is extremely rare. Due to its rarity, there is no consensus for diagnosis and treatment for undifferentiated liver tumor with OGCs. Definitive diagnosis comes from surgery, so there is often a long delay in diagnosis following the occurence of symptoms. This case described an extremely rare case of undifferentiated liver tumor with OGCs in detail and summarized the previously published cases based on liver tumor with OGCs from August 1980 to June 2021, in order to provide extensive evidence to improve preoperative diagnosis and management options.